Online Language Learning in Participatory Culture: Digital Pedagogy Practices in the Post-Pandemic Era - Youkyung Ju-Zaveroni; Seryun Lee (MDPI AG, 2023)
The COVID-19 pandemic dramatically accelerated the digitalisation of education around the world in a short period of time, which presented a unique opportunity for language teachers and policy makers to reconsider assumptions about language learning in higher education. Against this background, this study examines how digital pedagogy can enhance the experience of language learning in online settings in the post-pandemic era by drawing on a case study of educational activities developed during the pandemic for foreign language modules at a UK university. In particular, this study delves into the different dimensions of participatory culture in relation to digital pedagogy practices for language teaching and learning by adopting an interdisciplinary approach. Ultimately, we argue that online language education should aid students, i.e., the Gen Z cohort, in acquiring and developing digital literacy, or the capacity to communicate effectively by creating a variety of online texts and interreacting and collaborating with other people by means of various digital technologies. Therefore, it has also been argued that language teachers need to play a role as facilitators who can foster interactive, participatory environments to help students to develop student-centred, sustaining learning communities.